1997
DOI: 10.1103/physrevb.55.626
|View full text |Cite
|
Sign up to set email alerts
|

Topological order in the vortex-glass phase of high-temperature superconductors

Abstract: The stability of a vortex glass phase with quasi-long-range positional order is examined for a disordered layered superconductor. The role of topological defects is investigated using a detailed scaling argument, supplemented by a variational calculation. The results indicate that topological order is preserved for a wide range of parameters in the vortex glass phase. The extent of the stability regime is given in terms of a simple Lindemann-like criterion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
158
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(175 citation statements)
references
References 37 publications
17
158
0
Order By: Relevance
“…Note that the magnitude of this renormalization (i.e., the ratio F T /F D ) is mainly determined by the parameter ν −1 , see Eq. (29). Interestingly, in contrast to the case of the δT c pinning where ν appears as a result of the specific temperature dependence of g 0 , Eq.…”
Section: B Approximate Formulas Discussionmentioning
confidence: 89%
“…Note that the magnitude of this renormalization (i.e., the ratio F T /F D ) is mainly determined by the parameter ν −1 , see Eq. (29). Interestingly, in contrast to the case of the δT c pinning where ν appears as a result of the specific temperature dependence of g 0 , Eq.…”
Section: B Approximate Formulas Discussionmentioning
confidence: 89%
“…Nonetheless it has been shown that for strong enough disorder the Bragg glass phase is unstable against dislocation formation. [26][27][28] This suggests that the melting process could be ruled by topological defects ͑as discussed in Ref. 30͒ in analogy with two-dimensional theories of crystal melting.…”
Section: Grain-boundary-induced Meltingmentioning
confidence: 99%
“…25 At high enough disorder, the Bragg glass phase is found to be unstable against dislocation proliferation and one may expect the transition into an amorphous vortex glass. [26][27][28] The precise nature of this transition and, more generally, the mechanism underlying vortex lattice melting is still under debate. Typical melting theories are based on variants of the Lindemann criterion with disorder, 29 or involve dislocation proliferation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Point defects are naturally occurring, e.g., in ceramic high-T c materials in the form of oxygen vacancies, but can also be artificially introduced, for instance by electron irradiation [2]. The presence of weak point pinning centers destroys the long-range crystalline order of the low-temperature Abrikosov flux line lattice in the disorder-free system, to form either a genuine disordered vortex glass phase [3][4][5][6][7] or a Bragg glass state that is characterized by quasi long-range positional order [8][9][10][11][12][13]. The thermally induced first-order melting transition of the vortex lattice at elevated temperatures [14][15][16] is thereby replaced by a disorder-driven continuous phase transition between frustrated ('glassy') low-temperature states and a fluctuating flux liquid phase.…”
Section: Introductionmentioning
confidence: 99%